Globalisation and trade: A "New Economic Geography" perspective - Paolo Surico (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper presents a survey of the so-called 'New Economic Geography' (NEG) approach to International Trade, giving particular emphasis to the impact of labour mobility on the spatial distribution of economic activities across integrated countries. The liberalisation of international trade boosts industrial concentration according to a core-periphery pattern. However, when some factors of production, especially labour, are internationally immobile, a further reduction in trade costs scales up the importance of price and wage spatial differentials in the cost function of a typical firm compared to the importance of backward and forward linkages. This deters producers from setting up economic activities in the core and might in the end lead firms to a new dispersion towards less developed and more peripheral regions. In surveying the most recent contributions in this area, the paper sheds light on several shortcomings of the NEG literature in order to point out new directions for further research, with particular reference to studies concerning the European Union (EU).
Keywords: F10; F12; F15; 330; Agglomeration; economic integration; new economic geography; backward and forward linkages; labour mobility; wage differentials; Neue Außenhandelstheorie; Zentrum-Peripherie-Beziehung; Betrieblicher Standort; Arbeitsmobilität; Theorie; Neue ökonomische Geographie